Negative electrode composite current collector of non-negative electrode lithium battery and preparation method of negative electrode composite current collector
By employing a dual-gradient composite protective layer in a cathode-free lithium battery, the problems of uneven lithium deposition and battery structural stability were solved, achieving uniform lithium nucleation and improved battery performance, significantly enhancing cycle life and electrochemical stability.
Patent Information
- Application Number
- CN202511874684.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-12
- Publication Date
- 2026-03-20
AI Technical Summary
In negative electrode-free lithium batteries, uneven lithium deposition leads to lithium dendrite growth, causing issues with cycle stability and safety. The solid electrolyte interface layer is unstable, resulting in repeated consumption of lithium and electrolyte. During charging and discharging, changes in battery volume damage the electrolyte structure.
A dual-gradient composite protective layer design is adopted, which includes coating a metal nanoparticle@metal-organic framework protective layer and a dense lithium-friendly metal oxide layer on the surface of copper foil. The layers are prepared by solvothermal method and atomic layer deposition technology to construct a porous structure and a dense layer to buffer volume changes and promote uniform lithium nucleation.
It significantly reduces lithium nucleation overpotential, improves cycle life, provides uniform lithium deposition sites, and enhances the electrochemical performance and stability of the battery.
Smart Images

Figure CN121709629A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium battery technology, specifically relating to a negative electrode composite current collector for a negative electrodeless lithium battery and its preparation method. Background Technology
[0002] Traditional lithium-ion batteries use commercial graphite as the anode, but its theoretical capacity is only 372 mAh / g, which is insufficient to meet the ever-increasing energy demands. In contrast, lithium has a theoretical specific capacity as high as 3860 mAh / g and a redox potential as low as -3.04 V vs SHE. Therefore, using lithium metal to replace the graphite anode is considered a very promising strategy. Among various lithium metal batteries, anode-free lithium metal batteries (AFLMBs) can maximize the overall battery energy density, exceeding 500 Wh / kg, and are considered the ultimate choice for high-energy-density lithium metal batteries.
[0003] Invention patent CN116344828A provides a scheme for applying sulfonic acid-modified covalent organic framework materials to electrodeless lithium metal batteries, using copper foil modified with this material as the current collector. In this scheme, the introduction of sulfonic acid-modified covalent organic framework materials can improve the lithium-ion transport rate, thereby improving battery capacity and cycle stability to some extent. However, this type of covalent organic framework material does not incorporate metal nanoparticles, resulting in low intrinsic electronic conductivity, which can easily lead to significant polarization in electrodeless lithium battery systems, thus limiting further improvement in overall electrochemical performance.
[0004] Invention patent CN119920826A provides a method for preparing a negative electrode sheet for a negative electrodeless lithium battery. This method utilizes a lithiophilic active layer composed of silver nanowires and conductive particles to achieve relatively stable ion / electron transport channels at the atomic scale between the bulk phase and the interface. This helps to improve the disordered growth of lithium dendrites caused by uneven dispersion of nanowires and conductive particles, thereby enhancing the battery's cycle stability and coulombic efficiency. However, this lithiophilic active layer lacks a three-dimensional hierarchical porous structure, making it difficult to effectively buffer the volume change of lithium metal during deposition and providing a more efficient ion and electron transport network. This may lead to a decrease in lithium deposition binding energy, limiting further improvements in battery performance.
[0005] Currently, negative electrode-free lithium batteries still face three major challenges: 1. Uneven lithium deposition leads to lithium dendrite growth, which in turn causes cycle stability and safety issues; 2. Unstable solid electrolyte interphase (SEI) layer and limited lithium inventory lead to repeated consumption of lithium and electrolyte, resulting in significant "dead lithium" problems; 3. Drastic changes in battery volume during charging and discharging can disrupt the stable structure of the electrolyte. Summary of the Invention
[0006] To address the problem of uneven lithium deposition leading to dendrite formation in existing electrodeless lithium batteries, this invention provides a method for preparing electrodeless composite current collectors. This invention employs a dual-gradient composite protective layer design strategy, which consists of two layers: a metal nanoparticle (MNP)@metal-organic framework (MOF-NH2) protective layer is coated on a copper foil surface, followed by the deposition of a dense lithium-loving metal oxide layer. The dual gradient refers to a dual gradient design in both structure and function: the structural gradient refers to the transition from the porous composite layer at the bottom to the dense metal layer at the top; the functional gradient refers to the lower layer primarily handling volume buffering and ion / electron conduction, while the upper layer guides uniform nucleation and interface stabilization.
[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: A method for preparing a negative electrode composite current collector for a negative electrodeless lithium battery includes the following steps: (1) Metal nanoparticles@metal-organic framework composite material MNP@MOF-NH2 was prepared by solvothermal method; (2) Add the composite material MNP@MOF-NH2 prepared in step (1) and the conductive agent and binder to the solvent, mix and stir evenly to obtain the negative electrode coating slurry, coat it on the surface of the negative electrode current collector foil, and form the first coating layer after drying. (3) The negative electrode current collector foil coated with the first coating layer in step (2) is placed in the reaction chamber of the atomic layer deposition equipment. Then, by alternating feeding deposition method, metal source and gas are introduced to generate a dense lithium-loving metal oxide layer to form the second coating layer. After drying, a dual gradient composite protective layer, i.e. negative electrode composite current collector for lithium batteries without negative electrode, is obtained.
[0008] Further, the preparation method of the metal nanoparticle@metal-organic framework composite material MNP@MOF-NH2 in step (1) is as follows: Metal-organic framework material MOF-NH2 containing polar groups, metal precursor, and hexadecyltrimethylammonium chloride (CTAC) are added to N,N-dimethylformamide (DMF) and stirred evenly; then, the evenly mixed solution is placed in a polytetrafluoroethylene reactor, sealed with a stainless steel liner, and placed in an oil bath for solvothermal reaction by heating and stirring. After cooling to room temperature, the generated solid powder is collected by centrifugation, thoroughly washed with DMF and acetone, and then vacuum dried to obtain the metal nanoparticle@metal-organic framework composite material MNP@MOF-NH2. The amino (-NH2) polar groups in the MOF-NH2 material can effectively adsorb lithium ions and regulate their local concentration distribution as Lewis base sites, thereby guiding the uniform nucleation and deposition of lithium metal and inhibiting the formation of lithium dendrites; at the same time, the above-mentioned specific MOF-NH2 material has a regular porous structure and good thermal / chemical stability, providing an ideal confined space and stable framework for the subsequent in-situ growth of metal nanoparticles.
[0009] Furthermore, the metal-organic framework material MOF-NH2 containing polar groups is any one of NH2-MOF-5, NH2-HKUST-1, NH2-MIL-101, NH2-UIO-66, and NH2-ZIF-8; the metal precursor is a Mg-containing metal-organic framework material. 2+ Zn 2+ Sn 4+ or Ag 1+ The selected metal ions are any of the following nitrates. The nitrates of the chosen metal ions are readily reduced under solvothermal conditions, and these metals (or their alloys / oxides) themselves possess high lithiophilicity or can serve as nucleation sites for lithium metal deposition. More importantly, these metal precursors can generate nanoparticles in situ within the channels or surface of MOF-NH2, forming an MNP@MOF-NH2 composite structure. This structure combines the regular channels of the MOF with the catalytic / lithiophilic properties of the metal nanoparticles, synergistically enhancing the current collector's ability to regulate lithium deposition behavior.
[0010] Furthermore, the molar ratio of the metal-organic framework material containing polar groups to the metal precursor is (1~10):(1~5), and the molar ratio of the metal precursor to hexadecyltrimethylammonium chloride is (0.1~1 mmol):(50~200 mg).
[0011] Furthermore, the temperature of the solvothermal reaction is 80~160 ℃, and the time is 6~24 hours.
[0012] Furthermore, in step (2), the conductive agent is any one of carbon black, acetylene black, Ketjen black, vapor-grown carbon fiber, and carbon nanotubes, and the adhesive is any one of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, and polyacrylate. The mass ratio of the composite material, conductive agent, and adhesive is (90~98):(1~8):(3~9).
[0013] Furthermore, in step (2), the solvent is one or more of deionized water, N-methylpyrrolidone, and N,N-dimethylformamide, the solid content of the negative electrode coating slurry is 30%-60%, and the thickness of the first coating layer is 5-20 μm. Controlling the thickness of the first coating layer to 5-20 μm is crucial. If the thickness is less than 5 μm, there are insufficient lithiophilic nucleation sites, making it difficult to effectively guide large-area uniform lithium deposition; if the thickness is greater than 20 μm, it will unnecessarily increase the weight and volume of the battery's inactive materials, and may lead to increased ion transport distance and increased interfacial impedance due to an excessively thick coating, thereby affecting the battery's energy density and rate performance.
[0014] Furthermore, in step (3), the coating current collector is placed in the ALD reaction chamber of the atomic layer deposition equipment. Under the condition of 200°C, high-purity nitrogen is used as the carrier gas, and zinc metal source and oxygen source are alternately introduced. The zinc metal source is at least one of diethylzinc (Zn(C2H5)2), zinc chloride (ZnCl2), bis(diethylamino)zinc (BDEAZ) or zinc acetylacetonate (Zn(acac)2). The oxygen source is any one of deionized water, oxygen plasma, or hydrogen peroxide.
[0015] Furthermore, the parameters of the alternating feed deposition method in step (3) are: pulse time: 1~10s, carrier gas flow rate: 50~500 sccm, sweep time: 5~30s, process cycle: 10~500 cycles; the thickness of the second coating layer is 10-300 nm.
[0016] The present invention also provides a negative electrode composite current collector for a negative electrode-free lithium battery prepared by the aforementioned preparation method. The beneficial effects of this invention: This invention aims to synergistically solve multiple problems by constructing a bilayer structure of "dense lithiophilic layer + porous metal-organic framework and metal particle composite layer": the upper lithiophilic metal oxide induces uniform lithium nucleation and reduces the deposition barrier; the lower MOF network structure provides a spatial confinement effect to accommodate and separate lithium deposition; in addition, the polar groups contained in the MOF promote Li... + Desolvation and transport: Metal nanoparticles accelerate ion / electron transport. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 This is a schematic diagram of the negative electrode composite current collector, i.e., the dual-gradient composite protective layer structure, for a negative electrode-free lithium battery. 1. Copper foil current collector, 2. MNP@MOF-NH2 coating, 3. ALD deposition coating.
[0019] Figure 2 The lithium deposition and stripping voltage curves are for different composite layer electrodes. Detailed Implementation
[0020] The present invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make some non-essential improvements and adjustments based on the above-described invention.
[0021] This invention provides a method for preparing a negative electrode composite current collector for a negative electrode-free lithium battery, comprising the following steps: (1) Metal nanoparticles@metal-organic framework composite material MNP@MOF-NH2 was prepared by solvothermal method; (2) Add the composite material MNP@MOF-NH2 prepared in step (1) and the conductive agent and binder to the solvent, mix and stir evenly to obtain the negative electrode coating slurry, coat it on the surface of the negative electrode current collector foil, and form the first coating layer after drying. (3) The negative electrode current collector foil coated with the first coating layer in step (2) is placed in the reaction chamber of the atomic layer deposition equipment. Then, by alternating feeding deposition method, metal source and gas are introduced to generate a dense lithium-loving metal oxide layer to form the second coating layer. After drying, a dual gradient composite protective layer, i.e. negative electrode composite current collector for lithium batteries without negative electrode, is obtained.
[0022] In some embodiments, the preparation method of the metal nanoparticle@metal-organic framework composite material MNP@MOF-NH2 in step (1) is as follows: the metal-organic framework material MOF-NH2 containing polar groups, the metal precursor and hexadecyltrimethylammonium chloride CTAC are added to N,N-dimethylformamide DMF and stirred evenly; then the evenly mixed solution is placed in a polytetrafluoroethylene reactor, sealed with a stainless steel liner and placed in an oil bath, heated and stirred to carry out a solvothermal reaction, cooled to room temperature, centrifuged to collect the generated solid powder, washed thoroughly with DMF and acetone respectively, and then vacuum dried to obtain the metal nanoparticle@metal-organic framework composite material MNP@MOF-NH2.
[0023] In some embodiments, the metal-organic framework material MOF-NH2 containing polar groups is any one of NH2-MOF-5, NH2-HKUST-1, NH2-MIL-101, NH2-UIO-66, and NH2-ZIF-8; the metal precursor is a Mg-containing metal-organic framework material. 2 + Zn 2+ Sn 4+ or Ag 1+ Any one of the nitrates.
[0024] In some embodiments, the molar ratio of the metal-organic framework material containing polar groups to the metal precursor is (1~10):(1~5), and the molar ratio of the metal precursor to hexadecyltrimethylammonium chloride is (0.1~1 mmol):(50~200 mg).
[0025] In some embodiments, the temperature of the solvothermal reaction is 80~160 °C and the time is 6~24 hours.
[0026] In some embodiments, the conductive agent in step (2) is any one of carbon black, acetylene black, Ketjen black, vapor-grown carbon fiber, and carbon nanotubes, and the adhesive is any one of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, and polyacrylate. The mass ratio of the composite material, conductive agent, and adhesive is (90~98):(1~8):(3~9).
[0027] In some embodiments, the solvent in step (2) is one or more of deionized water, N-methylpyrrolidone, and N,N-dimethylformamide, the solid content of the negative electrode coating slurry is 30%-60%, and the thickness of the first coating layer is 5-20 μm.
[0028] In some embodiments, in step (3), the coating current collector is placed in the ALD reaction chamber of the atomic layer deposition equipment, and high-purity nitrogen is used as the carrier gas at 200°C. A zinc metal source and an oxygen source are alternately introduced. The zinc metal source is at least one of diethylzinc (Zn(C2H5)2), zinc chloride (ZnCl2), bis(diethylamino)zinc (BDEAZ) or zinc acetylacetonate (Zn(acac)2), and the oxygen source is any one of deionized water, oxygen plasma, or hydrogen peroxide.
[0029] In some embodiments, the parameters of the alternating feed deposition method in step (3) are: pulse time: 1~10s, carrier gas flow rate: 50~500 sccm, sweep time: 5~30s, process cycle: 10~500 cycles; the thickness of the second coating layer is 10-300 nm.
[0030] Example 1 The steps of a method for preparing a negative electrode composite current collector for a negative electrode-free lithium battery are as follows: (1) Preparation of metal-organic framework material containing polar groups (NH2-MOF-5): Take 1 mmol of zinc nitrate hexahydrate and 1 mmol of 2-aminoterephthalic acid, and pour them into 200 mL of N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a flask, put it in an oil bath at 100 °C, heat for 10 hours, cool to room temperature, centrifuge to collect the generated solid powder, wash three times with ethanol, and then vacuum dry at 60 °C for 4 hours.
[0031] (2) Take 0.5 mmol NH2-MOF-5, 0.1 mmol Mg(NO3)2 and 50 mg hexadecyltrimethylammonium chloride (CTAC) into 100 mL N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a polytetrafluoroethylene reactor, seal it with a stainless steel liner, and place it in an oil bath at 120 ℃. Heat and stir for 12 hours. After cooling to room temperature, centrifuge to collect the generated solid powder, wash it thoroughly three times with DMF and acetone, and then vacuum dry it at 60 ℃ for 4 hours to obtain Mg@NH2-MOF-5.
[0032] (3) Mg@NH2-MOF-5, conductive agent superconducting carbon black, binder sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in deionized water at a mass ratio of 96:1:2:1 to prepare a slurry with a solid content of 45%. The slurry is coated with an adjustable doctor blade to a thickness of 10 μm on the copper foil current collector 1. After drying, the first coating layer, namely MNP@MOF-NH2 coating 2, is formed.
[0033] (4) Place the copper foil current collector (electrode) coated with MNP@MOF-NH2 after drying in step (3) into the reaction chamber of the atomic layer deposition (ALD) equipment. Under the condition of 200 ℃, high-purity nitrogen is used as the carrier gas, and diethylzinc (Zn(C2H5)2) (pulse time: 1.5 s, carrier gas flow rate: 100 sccm) and deionized water (pulse time: 10 s, carrier gas flow rate: 80 sccm) are introduced alternately. The sweeping time is 10 s. After the process is cycled 50 times and the temperature of the reaction chamber is naturally cooled, a dense lithium-loving ZnO coating, i.e. the second coating, is formed. The electrode is taken out to obtain ZnO / Mg@NH2-MOF-5, in which the dense lithium-loving ZnO coating, i.e. the ALD deposition coating 3, is 10 nm.
[0034] (5) After drying at 80 °C for 12 hours, a negative electrode composite current collector for lithium batteries without negative electrodes is obtained.
[0035] Example 2 The steps of a method for preparing a negative electrode composite current collector for a negative electrode-free lithium battery are as follows: (1) Preparation of metal-organic framework material containing polar groups (NH2-HKUST-1): Take 1 mmol of copper acetate and 1 mmol of 2-amino-1,3,5-benzenetricarboxylic acid, and pour them into 200 mL of N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a flask, put it in an oil bath at 110 °C, heat for 12 hours, cool to room temperature, centrifuge to collect the generated solid powder, wash three times with ethanol, and then vacuum dry at 60 °C for 4 hours.
[0036] (2) Take 0.5 mmol NH2-HKUST-1, 0.2 mmol AgNO3 and 100 mg hexadecyltrimethylammonium chloride (CTAC) into 100 mL N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a polytetrafluoroethylene reactor, seal it with a stainless steel liner and place it in an oil bath at 130 ℃. Heat and stir for 18 hours. After cooling to room temperature, collect the generated solid powder by centrifugation, wash it thoroughly three times with DMF and acetone respectively, and then dry it under vacuum at 60 ℃ for 4 hours to obtain Ag@NH2-HKUST-1.
[0037] (3) Ag@NH2-HKUST-1, conductive agent superconducting carbon black, binder sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in deionized water at a mass ratio of 93:3:2:2 to make a slurry with a solid content of 35%. The slurry is coated on copper foil with an adjustable scraper with a thickness of 5 μm and then dried to form the first coating layer.
[0038] (4) The dried electrode sheet from step (3) is placed in the reaction chamber of an atomic layer deposition (ALD) apparatus. Under conditions of 200 °C, high-purity nitrogen is used as the carrier gas, and zinc chloride (ZnCl2) (pulse time: 3 s, carrier gas flow rate: 150 sccm) and hydrogen peroxide (pulse time: 5 s, carrier gas flow rate: 80 sccm) are introduced alternately. The purge time is 10 s. After 100 cycles of the process and natural cooling of the reaction chamber, ZnO / Ag@NH2-HKUST-1 is obtained, in which the dense lithium-loving ZnO coating is 20 nm.
[0039] (5) After drying at 80 °C for 12 hours, a current collector without negative electrode double gradient composite protective layer is obtained.
[0040] Example 3 The steps of a method for preparing a negative electrode composite current collector for a negative electrode-free lithium battery are as follows: (1) Preparation of metal-organic framework material containing polar groups (NH2-MIL-101): Take 1 mmol of chromium nitrate and 1 mmol of 2-aminoterephthalic acid, and pour them into 200 mL of N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a flask, put it in an oil bath at 100 °C, heat for 10 hours, cool to room temperature, centrifuge to collect the generated solid powder, wash three times with ethanol, and then vacuum dry at 60 °C for 4 hours.
[0041] (2) Take 0.5 mmol NH2-MIL-101, 0.3 mmol Zn(NO3)2 and 80 mg hexadecyltrimethylammonium chloride (CTAC) into 100 mL N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a polytetrafluoroethylene reactor, seal it with a stainless steel liner, and place it in an oil bath at 100 ℃. Heat and stir for 10 hours. After cooling to room temperature, collect the generated solid powder by centrifugation, wash it thoroughly three times with DMF and acetone, and then dry it under vacuum at 60 ℃ for 4 hours to obtain Zn@NH2-MIL-101.
[0042] (3) Zn@NH2-MIL-101, superconducting carbon black as a conductive agent, sodium carboxymethyl cellulose as a binder, and styrene-butadiene rubber are mixed in deionized water at a mass ratio of 95:2:2:1 to make a slurry with a solid content of 40%. The slurry is coated with a 15μm thick slurry onto copper foil using an adjustable scraper. After drying, it forms the bottom layer, which is also the first coating layer.
[0043] (4) The dried electrode sheet from step (3) is placed in the reaction chamber of an atomic layer deposition (ALD) apparatus. High-purity nitrogen is used as the carrier gas at 200 °C. Bis(diethylamino)zinc (BDEAZ) (pulse time: 3 s, carrier gas flow rate: 200 sccm) and deionized water (pulse time: 3 s, carrier gas flow rate: 500 sccm) are introduced alternately. The purge time is 20 s. After 75 process cycles and natural cooling of the reaction chamber, ZnO / Zn@NH2-MIL-101 is obtained, in which the dense lithium-loving ZnO coating is 15 nm.
[0044] (5) After drying at 80 °C for 12 hours, a current collector without negative electrode double gradient composite protective layer is obtained.
[0045] Example 4 The steps of a method for preparing a negative electrode composite current collector for a negative electrode-free lithium battery are as follows: (1) Preparation of metal-organic framework material containing polar groups (NH2-UiO-66): Take 1 mmol of zirconium chloride and 1 mmol of 2-aminoterephthalic acid, and pour them into 200 mL of N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a flask, put it in an oil bath at 130 °C, heat for 8 hours, cool to room temperature, centrifuge to collect the generated solid powder, wash three times with ethanol, and then vacuum dry at 60 °C for 4 hours.
[0046] (2) Take 0.5 mmol NH2-UiO-66, 0.4 mmol AgNO3 and 150 mg hexadecyltrimethylammonium chloride (CTAC) into 100 mL N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a polytetrafluoroethylene reactor, seal it with a stainless steel liner and place it in an oil bath at 140 ℃. Heat and stir for 12 hours. After cooling to room temperature, centrifuge to collect the generated solid powder. Wash it thoroughly three times with DMF and acetone respectively. Then dry it under vacuum at 60 ℃ for 4 hours to obtain Ag@NH2-UiO-66.
[0047] (3) Ag@NH2-UiO-66, conductive agent superconducting carbon black, binder sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in deionized water at a mass ratio of 94:3:2:1 to make a slurry with a solid content of 50%. The slurry is coated on copper foil with an adjustable scraper to form a 20 μm slurry as the bottom layer.
[0048] (4) The electrode after drying in step (3) is placed in the reaction chamber of an atomic layer deposition (ALD) device. High-purity nitrogen is used as the carrier gas at 200 °C. Diethyl zinc (Zn(C2H5)2) (pulse time: 5 s, carrier gas flow rate: 400 sccm) and oxygen plasma (pulse time: 6 s, carrier gas flow rate: 400 sccm) are introduced alternately. The sweep time is 15 s. After 400 cycles of the process and natural cooling of the reaction chamber, the electrode is taken out to obtain ZnO / Ag@NH2-UiO-66, in which the dense lithium-loving ZnO coating is 100 nm.
[0049] (5) After drying at 80 °C for 12 hours, a current collector without negative electrode double gradient composite protective layer is obtained.
[0050] Example 5 The steps of a method for preparing a negative electrode composite current collector for a negative electrode-free lithium battery are as follows: (1) Preparation of metal-organic framework material containing polar groups (NH2-ZIF-8): Take 1 mmol of zinc nitrate hexahydrate, 1 mmol of 2-methylimidazole, and 1 mmol of 2-aminoimidazole, and pour them into 200 mL of N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a flask, put it in an oil bath at 150 °C, heat for 12 hours, cool to room temperature, centrifuge to collect the generated solid powder, wash three times with ethanol, and then vacuum dry at 60 °C for 4 hours.
[0051] (2) Take 0.5 mmol NH2-ZIF-8, 0.5 mmol Sn(NO3)4 and 180 mg hexadecyltrimethylammonium chloride (CTAC) into 100 mL N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a polytetrafluoroethylene reactor, seal it with a stainless steel liner, and place it in an oil bath at 160 ℃. Heat and stir for 24 hours. After cooling to room temperature, centrifuge to collect the generated solid powder, wash it thoroughly three times with DMF and acetone, and then vacuum dry it at 60 ℃ for 4 hours to obtain Sn@NH2-ZIF-8.
[0052] (3) Sn@NH2-ZIF-8, conductive agent superconducting carbon black, binder sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in deionized water at a mass ratio of 93:3:2:2 to make a slurry with a solid content of 60%. The slurry is coated on copper foil with an adjustable scraper to form a 12 μm slurry as the bottom layer.
[0053] (4) Place the dried electrode sheet from step (3) into the reaction chamber of an atomic layer deposition (ALD) device. Under conditions of 200 °C, high-purity nitrogen is used as the carrier gas. Zinc acetylacetonate (Zn(acac)2) (pulse time: 2 s, carrier gas flow rate: 200 sccm) and deionized water (pulse time: 3 s, carrier gas flow rate: 300 sccm) are introduced alternately. The sweeping time is 15 s. After 500 cycles of the process and natural cooling of the reaction chamber, the electrode sheet is removed to obtain ZnO / Sn@NH2-ZIF-8, in which the dense lithium-loving ZnO coating is 200 nm.
[0054] (5) After drying at 80 °C for 12 hours, a current collector without negative electrode double gradient composite protective layer is obtained.
[0055] Comparative Example 1 The steps of a method for preparing a negative electrode composite current collector for a negative electrode-free lithium battery are as follows: Copper foil is used as the negative electrode current collector for a non-negative electrode lithium metal battery, and the dual-gradient protective layer of this application is not coated.
[0056] Comparative Example 2 The steps of a method for preparing a negative electrode composite current collector for a negative electrode-free lithium battery are as follows: Without the addition of Mg@NH2-MOF coating, the other components and preparation methods are basically the same as in Example 1, and the specific steps are as follows: (1) The copper foil was placed in the reaction chamber of the atomic layer deposition (ALD) equipment. High-purity nitrogen was used as the carrier gas at 200 °C. Diethyl zinc (Zn(C2H5)2) (pulse time: 1.5 s, carrier gas flow rate: 100 sccm) and deionized water (pulse time: 10 s, carrier gas flow rate: 80 sccm) were introduced alternately. The sweep time was 10 s. After 50 cycles of the process and natural cooling of the reaction chamber, the electrode was removed to obtain a dense lithium-loving ZnO coating with a thickness of 10 nm.
[0057] (2) After drying at 80 °C for 12 hours, a single-layer current collector without negative electrode is obtained.
[0058] Comparative Example 3 The steps of a method for preparing a negative electrode composite current collector for a negative electrode-free lithium battery are as follows: Without performing the atomic layer deposition (ALD) step in the examples, the other components and preparation methods are basically the same as in Example 1, and the specific steps are as follows: (1) Preparation of metal-organic framework material containing polar groups (NH2-MOF-5): Take 1 mmol of zinc nitrate hexahydrate and 1 mmol of 2-aminoterephthalic acid, and pour them into 200 mL of N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a flask, put it in an oil bath at 100 °C, heat for 10 hours, cool to room temperature, centrifuge to collect the generated solid powder, wash three times with ethanol, and then vacuum dry at 60 °C for 4 hours.
[0059] (2) Take 0.5 mmol NH2-MOF-5, 0.1 mmol Mg(NO3)2 and 50 mg hexadecyltrimethylammonium chloride (CTAC) into 100 mL N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a polytetrafluoroethylene reactor, seal it with a stainless steel liner, and place it in an oil bath at 120 ℃. Heat and stir for 12 hours. After cooling to room temperature, centrifuge to collect the generated solid powder, wash it thoroughly three times with DMF and acetone, and then vacuum dry it at 60 ℃ for 4 hours to obtain Mg@NH2-MOF-5.
[0060] (3) Mg@NH2-MOF-5, conductive agent superconducting carbon black, binder sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in deionized water at a mass ratio of 96:1:2:1 to make a slurry with a solid content of 45%. The slurry is coated with an adjustable scraper to a thickness of 10 μm on copper foil as a base layer.
[0061] (4) After drying at 80 °C for 12 hours, a single-layer current collector without negative electrode is obtained.
[0062] Comparative Example 4 The steps of a method for preparing a negative electrode composite current collector for a negative electrode-free lithium battery are as follows: Without metal nanoparticle doping, the other components and preparation methods are basically the same as in Example 1, and the specific steps are as follows: (1) Preparation of metal-organic framework material containing polar groups (NH2-MOF-5): Take 1 mmol of zinc nitrate hexahydrate and 1 mmol of 2-aminoterephthalic acid, and pour them into 200 mL of N,N-dimethylformamide (DMF) and stir well. Then place the well mixed solution in a flask, put it in an oil bath at 100 °C, heat for 10 hours, cool to room temperature, centrifuge to collect the generated solid powder, wash three times with ethanol, and then vacuum dry at 60 °C for 4 hours.
[0063] (2) NH2-MOF-5, conductive agent superconducting carbon black, binder sodium carboxymethyl cellulose and styrene-butadiene rubber are mixed in deionized water at a mass ratio of 96:1:2:1. The slurry has a solid content of 45%. The slurry is coated with an adjustable scraper to a thickness of 10 μm on copper foil as the bottom layer.
[0064] (3) Place the dried electrode sheet from step (1) into the reaction chamber of an atomic layer deposition (ALD) apparatus. Under conditions of 200 °C, high-purity nitrogen is used as the carrier gas. Diethyl zinc (Zn(C2H5)2) (pulse time: 1.5 s, carrier gas flow rate: 100 sccm) and deionized water (pulse time: 10 s, carrier gas flow rate: 80 sccm) are introduced alternately. The sweeping time is 10 s. After 50 cycles of the process and natural cooling of the reaction chamber, the electrode sheet is removed to obtain a dense lithium-affinity coating of ZnO / NH2-MOF-5.
[0065] (4) After drying at 80 °C for 12 hours, a current collector without negative electrode double gradient composite protective layer is obtained.
[0066] The negative electrode composite current collectors prepared in Examples 1-5 and Comparative Examples 1-4 were assembled into coin cells for performance testing. Lithium sheets were used as the counter electrode. The test results are shown in Table 1.
[0067] Table 1 Lithium nucleation overpotentials in different current collector composite layers Examples 1-5 of this invention employ a current collector with a "dual-gradient composite protective layer," which exhibits significantly superior electrochemical performance compared to all comparative examples. Specifically, the lithium nucleation overpotential is drastically reduced from -127.7 mV in Comparative Example 1 (bare copper foil) to an extremely low range of -23.1 mV to -29.6 mV, and the cycle life is significantly increased from 113 hours in Comparative Example 1 to over 430 hours (the optimal example 1 reaches 513 hours). Furthermore, compared to Comparative Example 2 (without the lower MOF composite layer, 280 hours), Comparative Example 3 (without the upper dense lithophile oxide layer, 293 hours), and Comparative Example 4 (MOF composite layer without metal nanoparticles, 298 hours), which only have partial protective layers, this invention demonstrates superior overall performance in providing uniform nucleation sites, buffering volume changes, and promoting ion transport through the synergistic effect of the upper dense lithophile oxide layer and the lower porous MNP@MOF composite layer.
[0068] The foregoing has shown and described the basic principles and main features of the present invention, as well as its advantages. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a negative electrode composite current collector for a negative electrodeless lithium battery, characterized in that... Includes the following steps: (1) Metal nanoparticles@metal-organic framework composite material MNP@MOF-NH2 was prepared by solvothermal method; (2) Add the composite material MNP@MOF-NH2 prepared in step (1) and the conductive agent and binder to the solvent, mix and stir evenly to obtain the negative electrode coating slurry, coat it on the surface of the negative electrode current collector foil, and form the first coating layer after drying. (3) The negative electrode current collector foil coated with the first coating layer in step (2) is placed in the reaction chamber of the atomic layer deposition equipment. Then, by alternating feeding deposition method, metal source and gas are introduced to generate a dense lithium-loving metal oxide layer to form the second coating layer. After drying, a dual gradient composite protective layer, i.e. negative electrode composite current collector for lithium batteries without negative electrode, is obtained.
2. The method for preparing the negative electrode composite current collector for a negative electrodeless lithium battery according to claim 1, characterized in that, The preparation method of the metal nanoparticle@metal-organic framework composite material MNP@MOF-NH2 in step (1) is as follows: add the metal-organic framework material MOF-NH2 containing polar groups, the metal precursor and hexadecyltrimethylammonium chloride CTAC to N,N-dimethylformamide DMF and stir evenly; then place the evenly mixed solution in a polytetrafluoroethylene reactor, seal it with a stainless steel liner and place it in an oil bath, heat and stir to carry out a solvothermal reaction, cool to room temperature, centrifuge to collect the generated solid powder, wash it thoroughly with DMF and acetone respectively, and then vacuum dry to obtain the metal nanoparticle@metal-organic framework composite material MNP@MOF-NH2.
3. The method for preparing the negative electrode composite current collector for a negative electrodeless lithium battery according to claim 2, characterized in that, The metal-organic framework material MOF-NH2 containing polar groups is any one of NH2-MOF-5, NH2-HKUST-1, NH2-MIL-101, NH2-UIO-66, and NH2-ZIF-8; the metal precursor is a Mg-containing metal-organic framework material. 2+ Zn 2+ Sn 4+ or Ag 1+ Any one of the nitrates.
4. The method for preparing the negative electrode composite current collector for a negative electrodeless lithium battery according to claim 2, characterized in that, The molar ratio of the metal-organic framework material containing polar groups to the metal precursor is (1~10):(1~5), and the molar ratio of the metal precursor to hexadecyltrimethylammonium chloride is (0.1~1 mmol):(50~200 mg).
5. The method for preparing the negative electrode composite current collector for a negative electrodeless lithium battery according to claim 2, characterized in that, The temperature of the solvothermal reaction is 80~160 ℃, and the time is 6~24 hours.
6. The method for preparing the negative electrode composite current collector for a negative electrodeless lithium battery according to claim 1, characterized in that, In step (2), the conductive agent is any one of carbon black, acetylene black, Ketjen black, vapor-grown carbon fiber, and carbon nanotubes, and the adhesive is any one of polyvinylidene fluoride, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, and polyacrylate. The mass ratio of the composite material, conductive agent, and adhesive is (90~98):(1~8):(3~9).
7. The method for preparing the negative electrode composite current collector for a negative electrodeless lithium battery according to claim 1, characterized in that, In step (2), the solvent is one or more of deionized water, N-methylpyrrolidone, and N,N-dimethylformamide, the solid content of the negative electrode coating slurry is 30%-60%, and the thickness of the first coating layer is 5-20 μm.
8. The method for preparing the negative electrode composite current collector for a negative electrodeless lithium battery according to claim 1, characterized in that, In step (3), the coating current collector is placed in the ALD reaction chamber of the atomic layer deposition equipment. Under the condition of 200°C, high-purity nitrogen is used as the carrier gas, and zinc metal source and oxygen source are alternately introduced. The zinc metal source is at least one of diethylzinc (Zn(C2H5)2), zinc chloride (ZnCl2), bis(diethylamino)zinc (BDEAZ) or zinc acetylacetonate (Zn(acac)2). The oxygen source is any one of deionized water, oxygen plasma, or hydrogen peroxide.
9. The method for preparing the negative electrode composite current collector for a negative electrodeless lithium battery according to claim 1, characterized in that, The parameters for the alternating feed deposition method in step (3) are: pulse time: 1~10s, carrier gas flow rate: 50~500 sccm, sweep time: 5~30s, process cycle: 10~500 cycles; the thickness of the second coating layer is 10-300 nm.
10. The negative electrode composite current collector for a negative electrode-free lithium battery prepared by the preparation method according to claims 1-9.
Citation Information
Patent Citations
Negative-electrode-free lithium metal battery based on sulfonic-group-modified covalent organic framework material
CN116344828A
Negative pole piece, preparation method thereof, lithium battery without negative pole and lithium battery
CN119920826A
Cited By
A zinc-enriched carbon nanoflower current collector with a double inorganic passivation layer for a negative electrode-free lithium metal battery
CN122532253A